ITIL® 4 Foundation Revision guide (TSO (The Stationery Office), 2022)
This revision guide will help all those who are preparing to take their ITIL 4 Foundation examination. A practical portable pocket-size reference for easy review and testing. Key examination topics are outlined concisely covering concepts, guiding principles, the four dimensions of service management, the ITIL service value system, the service value chain and ITIL practices. Sample questions and hints and tips to pass your exam are also included to help with examination preparation. Written and endorsed by itSMF, this helpful study guide is essential reading for those who want to pass the ITIL 4 Foundation examination.